ANALISIS SURVIVAL PASIEN GAGAL GINJAL KRONIS DENGAN TERAPI HEMODIALISIS DI RSUD BULELENG - Syahrani, Luh Privinka Berta; Widarini, Ni Putu (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025DO - 10.24843/ACH.2025.v12.i01.p05, 2025)
ABSTRACT Chronic Kidney Disease (CKD) is a global public health problem with increasing prevalence and incidence, has a poor prognosis and requires high costs to treat. The results of the 2017 Global Burden of Disease study stated that CRF was the 15th cause of death in 2017. The 2013 Riskesdas data for the Bali Province stated that the prevalence of CRF in Buleleng Regency (0.3%) was ranked 2nd. Based on a preliminary study at the Buleleng Hospital, it was found that there were 144 patients with CRF undergoing HD in 2021. The aim of the study was to determine the factors that are thought to influence the survival time of CRF patients, as well as to compare the survival time of CRF patients undergoing HD at Buleleng Hospital in 2010. 2021. This research is a type of analytic observational research, with a historical cohort study design. The results of the analysis showed that 75% of patients were still alive after 186 days from the start of the patient undergoing HD. Factors that affected the survival of CRF patients undergoing hemodialysis at Buleleng General Hospital were gender (HR=2.62; 95% CI=1.221-5.639; p=0.05), number of comorbidities (HR=1.479; 95% CI= 1.004-2.177; p=0.047), anemia status (HR=0.393; 95% CI=0.171-0.901; p=0.027). From the results of this study, the government should be able to increase Posbindu PTM, through PTM prevention activities, especially regarding CRF. There is a need for preventive efforts to prevent CRF, with improvements to individual behavioral factors, namely diet, physical activity, drug consumption, smoking. There is a need for further consideration and study on decision making for the implementation of renal replacement therapy in CRF patients with comorbidities such as patients with anemia. Keywords:  Survival analysis, Chronic Kidney Disease, Hemodialysis